The influence of green marketing, shariah compliance, customer’s environmental awareness and customer’s satisfaction towards muslim consumer purchasing behavior in Kedah - Nur Aina, Mohd Jamil (2019)
Effort of business to protect the environment need support from the consumers to make it achieve their objective. Other than that, Muslims and non-Muslims seek for a products and services that follow Islamic principles in their operations and business. This is because of the cleanliness of Shariah compliance principles. In order to improve purchasing behavior of the consumers, hotel industry should enhance and stimulate their green marketing and Shariah compliance practices in their hotels. The purpose of this study is to identify the influence of green marketing, Shariah compliance, customer’s environmental awareness and customer’s satisfaction towards Muslim purchasing behavior at Kedah, Malaysia. Precisely, the objectives of this study are to investigate, examine and determine between the factors (green marketing, Shariah compliance, customer’s awareness and customer’s satisfaction) and consumers purchasing behavior. A random sampling technique was used to collect the respondents in Kedah, Malaysia. The study also used quantitative approach through structured questionnaires developed from previous research. A total of 403 online survey questionnaires were distributed through Whatsapp application and Facebook pages. The study used SPSS 25.0 to analyze the collected data. Methodologies such as Pearson Correlation and Multiple Regression Analysis were implemented in order to analyze the data collected. As a whole, the findings revealed that consumer purchasing behavior had positive relationship and significant with green marketing, Shariah compliance, customer’s awareness and customer’s satisfaction. Finally, this study concluded with discussion, limitations of the study and some suggestions for future researches.